Metastatic Prostate Cancer Manifesting as Cholestatic Jaundice: A Case Report and Review of the Literature - Deepak Ravindranathan; Emilie Elise Hitron; Greta Anne Russler; Yue Xue; Mehmet Asim Bilen (Case Reports in Oncological Medicine)
A paraneoplastic syndrome can often present as the first manifestation of an underlying malignancy. We report a patient who presented with cholestatic jaundice as a paraneoplastic syndrome from his newly diagnosed metastatic prostate cancer. He received initial treatment with androgen deprivation therapy followed by six cycles of docetaxel resulting in resolution of his cholestatic process, normalization of liver enzyme levels, and excellent biochemical and radiographic response. To the best of our knowledge, this is the first reported case of metastatic prostate cancer with cholestatic jaundice as a paraneoplastic phenomenon to be safely treated with androgen deprivation therapy and upfront docetaxel, reflecting the latest shift in the treatment of metastatic prostate cancer.